PELAYANAN PRIMA FAKULTAS ILMU SOSIAL (FIS) UNNES DALAM BIDANG AKADEMIK DAN KEMAHASISWAAN - Handoyo, Eko (Forum Ilmu Sosial, 2009)
The problems to be solved in this study are: (1) The types of academic and student services are provided by the Social Sciences Faculty?, (2) how far principles of public service pinsip applied in the Social Sciences Faculty provides academic and student services?, ( 3) Sejaumanakah academic and student services are organized Social Sciences Faculty is based on the Standard Public Service?, (4) How big is the level of customer satisfaction (students, stakehoulder, and communities) to academic and student services provided by the Social Sciences Faculty?. The purpose of this research is to solve the problems mentioned above.This research took the location of the Social Sciences Faculty, especially in the areas of student services at the 2nd foor of Building C7. Object of this research is excellent service performance demonstrated by the Social Sciences Faculty (FIS) Unit of analysis is the study of service providers implementing academic and student who coordinated the FIS and the Head of the TU leadership ranks of the faculty involved. The things that will be examined and dianalis in this study are: (1) the forms of academic services (booking courses, KRS printing, etc.), (2) application of the principles of public service organized by the Social Sciences Faculty , (3) application of public service standards in the service of academic and student affairs, (4) measuring the level of customer satisfaction (students and other stakehoulder) for academic and student services provided by the Social Sciences Faculty (FIS).Source of research data is the primary and secondary. A primary source is data obtained from the FIS service providers and students. Study sample as many as 96 people obtained by snowball sampling technique and incidental sampling. Secondary data obtained from the database of students, faculty profles, and SOP academic and student affairs. This research data collected through questionnaires, observation, interviews, and Focused Group Discussion (FGD). To test the validity of data, used triangulation methods. Further data were analyzed quantitatively and qualitatively. From the results of research and feld fndings, it can be concluded the following things: (1) academic and student services provided by the Social Sciences Faculty is in conformity with principles, principles, and service standards as set by the government, (2) students and stakeholders Other interests satisfed with the services provided by the Social Sciences Faculty, (3) the general performance of the Faculty of Social services better, but in some service elements still need improvement, namely the responsibilities of staff, assurance / compliance costs of service, speed of service, and certainty / precision service schedule. Based on our research, suggested the need for increased responsibility and speed of service by way of: (a) The unit leader should coordinate and synchronize routine tasks, (b) the leadership of the faculty and administration (the administration) should do the monitoring and evaluation of staff performance or employees, (c) the need for a refresher and increase staff competence in accordance with its tasks through